Rationale for Use of an FDA-Cleared Delivery System for Administration of Inhaled Nitric Oxide in Patients Undergoing Magnetic Resonance Imaging - Salas M; Potenziano JL; Acker J (Medical Devices: Evidence and Research, 2021)
Mauro Salas,1 Jim L Potenziano,2 Jaron Acker3 1Clinical Specialist, Children’s National Health System, Washington, DC, USA; 2Scientific Affairs, Mallinckrodt Pharmaceuticals, Bedminster, NJ, USA; 3Medical Device Marketing, Mallinckrodt Pharmaceuticals, Bedminster, NJ, USACorrespondence: Mauro SalasChildren’s National Health System, 111 Michigan Ave NW, Washington, DC 20010, USATel +1 202 602 4090Email MSalas@childrensnational.orgAbstract: Inhaled nitric oxide (iNO) is a pulmonary vasodilator approved for use to improve lung function in neonates > 34 weeks’ gestational age with hypoxic respiratory failure and pulmonary hypertension. Infants with severe respiratory disease frequently require magnetic resonance imaging (MRI) scans for evaluation of treatment and diagnosis of concurrent disease processes. Until 2015, incompatibility between the standard iNO delivery system components and the magnetic field within the MRI setting required iNO treatment to be interrupted for MRI, which could increase risk of deoxygenation and rebound pulmonary hypertension. In some cases, patients had to forego or delay MRI in order to maintain uninterrupted iNO delivery. The US Food and Drug Administration cleared the first iNO delivery system specifically modified for conditional use with MRI scanners (INOmax DSIR® Plus MRI) in 2015, based on the determination that the MRI-cleared system met the performance standards equivalent to the standard system. The system design and manufacturer risk management activities, as well as the regulatory requirements for clearance and continued use, provide necessary safeguards to ensure that high-risk neonates receive uninterrupted iNO in a safe manner. Anecdotal reports suggest that adoption of the MRI-cleared system may help optimize care for critically ill neonates who require concurrent administration of iNO and MRI scanning. Further research will be necessary to quantify the nature and magnitude of clinical improvements associated with adoption of the MRI iNO delivery system.Keywords: critical care, drug delivery systems, magnetic resonance imaging, newborn, nitric oxide